Comparison test of synthetic dyes with natural dyes on the quality of cotton sugar - Umar Alifudin; A Miftakhurrohmat A Miftakhurrohmat (Universitas Muhammadiyah Sidoarjo, 2015)
This study aims to comparesynthetic and natural colour on quality and characteristics of sugar cotton. The research was conducted in April-June 2014 at Laboratory of Product Development and Laboratory of Food Analysis, Faculty of Agriculture, Muhammadiyah University of Sidoarjo. The experiment was arranged in a randomized block design (RBD) with 7 treatment consisting:withoutcolour (control), addition of synthetic colourand natural colourwithin ratio 12 ml:0 g, 8 ml:16 g, 8 ml:32 g, 4 ml:16 g, 4 ml:24 g, and 0 ml:48 gr. The measured variables were chemical analysis (concentration of sucrose, glucose and fructose), physical analysis (volume, weight shrinkage, durability sugar cotton inside and outside plastic) and organoleptic analysis (color, taste, aroma, and texture). The data of chemical and physical analysis were analyzed by Anova followed by HSD 5%, while organoleptic was analyzed by Friedman test and method of De Garmo to find the best treatment. Comparison between synthetic colourand natural colour were significantlydifferent on the levels of sucrose, glucose, fructose, volume analysis, resilience in plastic and outer plastic resistance; and significantly affect the color and flavor, but not significantly different on taste and texture. Overall, the best treatment was without natural preservatives and artificial; but the all treatment with preservatives, synthetic colour of 8 ml treatment and 16 g natural colourwas the best treatment.